The Prophetic Hadith as evidence for Grammar: - Almatroudi, Ibrahim Sulaiman Ibrahim (Journal of Arabic Language Sciences and Literature, 2023)
In Islamic and Arabic Legacy there are issues where a satisfactory solution had not been reached yet; pens roam around these issues and flutter without much progress, in fact sometimes mystery is added proportionally to reflection upon them, one of those issues is The Arguing with Honorable Alhadith with Grammarians, first among those who rallied for it was Ibn Aldhaea Alandalusi in the seventh century, and followed down that path his pupil Abu Hayyan Alandalusi; then more argument was issued among Modern grammarians, to the point where you can not find a single paper where its author did not participate at one point in this same issue, be it in support or against it. The conclusion of modern studies is split into four main outcomes: 1) Acceptance of the claims of Ibn Aldhaea and his pupil Abo Hayyan that early grammarians did not argue with Alhadith or they did not argue with it enough. 2) That Ibn Malik and before him Ibn Tarawah and Ibn Kharoof, put The Alhadith in its rightful place. 3) Alhadith was present in Early Grammarians work even though sometimes it was not referenced back to Prophet Mohammed Peace be Upon Him. 4) Never has it been said that Early grammarians denied Arguing with Alhadith, not in their actions nor in their saying. These Four outcomes gave me a glimpse into this linguistic mystery, and I hope that I will succeed in finding a solution that gathers in itself something from each side, to produce a solution that satisfies everyone.  The methodology adopted for this study is a Descriptive method, with two main parts, the first being inductive in nature, where I collected the opinions of early and modern scholars about the argument with Al-Hadith by Grammarians; The second being analytical, by describing what the grammarians thought about Al-Hadith and their analysis of it, criticizing here and agreeing with it there. Some of the results of this research endeavor: - That the essence of argument with Al-Hadith was the fact that The Prophet Peace be upon him was Arabic, he would get the same treatment as any other arab by the grammarians, if considering the language and its rules he should pose no difference to any other individual, as Ibn Jinni said in his Khassaess, such conclusion is related to the grammarians by this study, it even go so far as to link their attitude toward arabs in general to an added evidence.
Keywords: Dilemma; Argument; Al-hadith; Arabic language; Grammarians